2005
DOI: 10.4073/csr.2005.5
|View full text |Cite
|
Sign up to set email alerts
|

Speech and Language Therapy Interventions for Children with Primary Speech and Language Delay or Disorder

Abstract: The aim of this Campbell systematic review is to examine the effectiveness of speech and language interventions for children with primary speech and language delay/disorder. Thirty‐six studies were found, based on a total of 1,500 children involved in thirty‐three randomised controlled trials. This Review concludes, on the basis of the available international studies in this field, that speech and language therapy generally has a positive effect on children with expressive phonological difficulties. The therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 74 publications
1
84
1
4
Order By: Relevance
“…35 Twentythree of these studies 95 also met criteria for this review and are included in Table 7, and 2 trials were unpublished. The review reported results in terms of standard mean differences (SMDs) in scores for a number of domains (phonology, syntax, and vocabulary).…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Twentythree of these studies 95 also met criteria for this review and are included in Table 7, and 2 trials were unpublished. The review reported results in terms of standard mean differences (SMDs) in scores for a number of domains (phonology, syntax, and vocabulary).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Search terms were determined by the investigators and a research librarian and are described elsewhere. 33 Articles were also obtained from recent systematic reviews, 34,35 reference lists of pertinent studies, reviews, editorials, and Web sites and by consulting experts. In addition, the investigators attempted to collect instruments and accompanying manuals; however, these materials are not generally available and must be purchased, which limited the evidence review to published articles.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…36 TheCochraneReviewofrandomizedcontrolled trials of a range of speech and language interventions for children with primary language impairment has demonstrated the potential benefit of such interventions, especially with young children and especially for those with speech and expressive language difficulties. 37 Clearly, it is possible to introduce environmental modifications that can stimulate the development of speech and language skills through a combination of direct instruction and the development of metacognitive skills that allow the children to acquire the requisite skills more efficiently. To date, the research literature would tend not to support the introduction of social skills training as such, especially in high incidence conditions, but social skills and pragmatics are not the same thing.…”
Section: Implications For Practicementioning
confidence: 99%
“…Systematic reviews support intervening for expressive language and phonological development for children with pronounced, clinical levels of difficulty. 4,5 Unfortunately, benefits to receptive language difficulties are less clear, and some interventions may even be contraindicated. 6 A related area of development that clearly shares common factors, is phonics, and specifically the role that this plays in the development of preliteracy skills.…”
mentioning
confidence: 99%